EXPLORING AT MOST TWIN OUTER PERFECT DOMINATION NUMBER FOR GENERAL BINARY TREE AND SOME SPECIAL GRAPHS. Issue 1 (May 2021) - Mahadevan, G.; Iravithul Basira, A.; Vimala Suganthi, M.
Abstract: A set S⊆ V(G) said to be an at most twin outer perfect dominating set if for every vertex v∈V-S, l⩽|N(v)∩S|⩽2 and < V-S> has at least one perfect matching. The minimum cardinality of at most twin outer perfect dominating set is called the at most twin outer perfect domination number and γ atop ( G ) denotes this number. This was initiated by G.Mahadevan.et.al., recently. Here we find this number for general Binary-tree. corona product of paths and cycles and lotus inside graph.